2015
DOI: 10.1111/fcsr.12120
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy: The Relationship to Saving Behavior in Low‐ to Moderate‐income Households

Abstract: This study was designed to explore financial literacy in low-to moderate-income households with regard to saving behavior. The study examined the low-to moderate-income household's decision to save regularly and their responses to three questions related to financial literacy and a self-reported perception of financial knowledge. Perceived financial knowledge and planning (usually or most of the time) were good indicators of the decision to save regularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 58 publications
4
32
0
9
Order By: Relevance
“…Also, people with high level of education and study major related to business also have a significant positive relationship with the probability of regular personal saving. It supports the findings from Mahdzan & Tabiani (2013) and Henager & Mauldin (2015) in which actual financial knowledge is thought to be essential for best practices and positive financial behaviours such as having an emergency fund, saving regularly and saving for retirement. Moreover, also we can agree with Lusardi &Mitchell (2014), that efforts to better measure financial education are likely to pay off.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Also, people with high level of education and study major related to business also have a significant positive relationship with the probability of regular personal saving. It supports the findings from Mahdzan & Tabiani (2013) and Henager & Mauldin (2015) in which actual financial knowledge is thought to be essential for best practices and positive financial behaviours such as having an emergency fund, saving regularly and saving for retirement. Moreover, also we can agree with Lusardi &Mitchell (2014), that efforts to better measure financial education are likely to pay off.…”
Section: Resultssupporting
confidence: 87%
“…According to van Rooij et al (2012), those with higher levels of confidence in their financial knowledge are more likely to plan and save for retirement. Furthermore, Henager & Mauldin (2015) found that perceived financial knowledge is a strong indicator of saving behaviour, which supports the findings of Allgood & Walstad (2011) and Robb & Woodyard (2011). In their research, they point out that perceived financial knowledge is essential for best practices and positive financial behaviours such as paying off credit card balances, having an emergency fund, and saving for retirement.…”
Section: Actual and Perceived Financial Literacy And Financial Behavioursupporting
confidence: 62%
See 1 more Smart Citation
“…Economic factors including income, net worth, and homeownership determine saving decisions, and income and saving are closely related. Generally, as household income or lifetime earnings increases, the likelihood of saving increases (Avery & Kennickell, ; Chang, ; Henager & Mauldin, ; Rha et al., ; Yuh & Hanna, ). A similar relationship exists between household wealth and saving (Avery & Kennickell, ; Gutter et al., ; Mauldin et al., ; Yuh & Hanna, ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Low levels of financial literacy have been linked to suboptimal financial behaviour. In particular, individuals with low levels of financial literacy are less likely to save for unexpected expenses (Henager & Mauldin, ), have larger debts and engage more in high‐cost borrowing (Disney & Gathergood, ; Huston, ; Lusardi & Tufano, ). Moreover, a lack of financial literacy prevents individuals from preparing for retirement, making them vulnerable for future income shocks (Lusardi & Mitchell, , ).…”
Section: Introductionmentioning
confidence: 99%